Evaluation of a health trainer–led service for people with knee, hip and back pain. (November 2019) - Hurley, MV; Semple, A; Sibley, F; Walker, A
Aims: Chronic knee, hip and back pain is extremely prevalent. Management guidelines emphasise maintaining physical activity and healthy weight to reduce pain and improve physical and mental wellbeing. Unfortunately, few people receive support to make lifestyle changes. We evaluated whether a health trainer—led 'joint pain advice' (JPA) service delivering person-centred lifestyle coaching was feasible, acceptable and effective for people with knee, hip and back pain. Methods: Feasibility of delivering a JPA service was assessed by documenting whether the health trainers could deliver JPA and its uptake. Nine health trainers delivered JPA. Participants were offered up to four appointments. At each appointment, health trainers gave people information about their condition, co-developed care plans, suggested self-management strategies and used behavioural change techniques (motivational interviewing, goal-setting and action planning) to increase physical activity and reduce body weight. Pain, function, physical activity and body mass index (BMI) were collected at baseline, 3 weeks, 6 weeks and 6 months. Focus groups captured people's opinions of the service's effectiveness, acceptability and usefulness. Results: Of the 105 people who enquired about JPA, 85 (81%) used the service, after which their physical activity and function improved, and pain, use of analgesia and BMI decreased. They felt more knowledgeable and better motivated to adopt and maintain healthier behaviours. They attributed these improvements to the JPA service, because of its better consultations and collaborative holistic approach. Only a minority attended all four appointments because they felt they received sufficient advice from the initial appointments. The health trainers gained knowledge and skills to support clients with musculoskeletal conditions. Conclusions: Using a holistic, patient-centred approach, health trainers can deliver lifestyle advice to people with chronic knee, hip or back pain safely, effectively and efficiently. The service was popular with recipients and health trainers, and helped people adopt healthier lifestyles that lead to reduced pain and other clinical improvements.